A technical review of building-mounted wind power systems and a sample simulation model - SAĞLAM, ŞAFAK (My University, 2012)
Small scale wind turbines installed within the built environment is classified as micro generation technology. This paper reports the investigation results of wind power application in buildings. First, general information is given for common type of wind turbines are used on buildings. Second, the wind aerodynamics and wind flows over the buildings are investigated based on local meteorological data and local building characteristics. However, to receive the highest potential wind energy resource and avoid turbulent areas, the tool of Computational Fluid Dynamics (CFD) has to be used to model the annual wind flows over buildings to help analyze, locate, and design wind turbines on and around buildings. Three different sample models for buildings and rural residential areas are explained with CFD models. © 2011 Elsevier Ltd. All rights reserved.
Keywords: Building-mounted; CFD; Horizontal axis; Micro-wind; Vertical axis; Wind power